2021
DOI: 10.1007/s12308-021-00459-3
|View full text |Cite
|
Sign up to set email alerts
|

Blood cell morphology and COVID-19 clinical course, severity, and outcome

Abstract: COVID-19 infection affects different organs of the human body, and blood cells are not an exception. Peripheral blood smear (PBS) is a simple and available method to investigate blood cells’ morphologic changes. In this study, we aimed to determine the morphologic changes and abnormalities of COVID-19 patients and their relation to the patients’ clinical course. In this prospective cross-sectional study, we included 89 PCR-positive COVID-19 patients. A pathologist examined the PBS findings of these patients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 24 publications
2
15
2
Order By: Relevance
“…The peripheral smear findings in this study were compared to other similar studies carried out in different populations of the world. In a study conducted by Pezeshki et al [18] from Iran, the most frequent peripheral smear abnormalities were thrombocytopenia (78.7%), smudge cells (67.4%), normocytic normochromic anemia (54%), giant platelets (42.7%), atypical lymphocytes (36%), leukopenia (37.1%), leukocytosis (29.2%) and schistocytes (27%), unlike the present study (Table 10). In a study of leukocyte morphological changes in COVID-19 by Kannan et al [7] from India, the neutrophils showed acquired neutrophilic nuclear projections (ANNP), acquired Pelger-Huet anomaly (APHA), toxic granules and myeloid shift to the left while the lymphocytes showed plasmacytoid appearance (plasmacytoid lymphocytes) in comparison to the present study which showed neutrophils with ring nuclei and toxic granules.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The peripheral smear findings in this study were compared to other similar studies carried out in different populations of the world. In a study conducted by Pezeshki et al [18] from Iran, the most frequent peripheral smear abnormalities were thrombocytopenia (78.7%), smudge cells (67.4%), normocytic normochromic anemia (54%), giant platelets (42.7%), atypical lymphocytes (36%), leukopenia (37.1%), leukocytosis (29.2%) and schistocytes (27%), unlike the present study (Table 10). In a study of leukocyte morphological changes in COVID-19 by Kannan et al [7] from India, the neutrophils showed acquired neutrophilic nuclear projections (ANNP), acquired Pelger-Huet anomaly (APHA), toxic granules and myeloid shift to the left while the lymphocytes showed plasmacytoid appearance (plasmacytoid lymphocytes) in comparison to the present study which showed neutrophils with ring nuclei and toxic granules.…”
Section: Discussioncontrasting
confidence: 81%
“…The peripheral smear findings in this study were compared to other similar studies carried out in different populations of the world. In a study conducted by Pezeshki et al [ 18 ] from Iran, the most frequent peripheral smear abnormalities were thrombocytopenia (78.7%), smudge cells (67.4%), normocytic normochromic anemia (54%), giant platelets (42.7%), atypical lymphocytes (36%), leukopenia (37.1%), leukocytosis (29.2%) and schistocytes (27%), unlike the present study (Table 10 ).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Despite overall minor reduction of circulating platelets, COVID-19 is associated with increased levels of immature platelets, indicating enhanced platelet turnover ( 162 ). Blood smears of COVID-19 patients further revealed the presence of giant platelets, corroborating reports of increased MPV ( 47 , 163 , 164 ). Increased MPV is associated with disease severity ( 164 , 165 ) and acute kidney failure in COVID-19 ( 166 ), but interestingly not with ICU requirement ( 48 ).…”
Section: Contribution Of Platelets To Viral Pathologiessupporting
confidence: 85%
“…The most common findings were the presence of large granular, lymphoplasmoid, and Downey cell-like reactive lymphocytes, pseudo Pelger-Huet anomaly, and morphologically changed monocytes ( 30 - 40 ). Other changes less frequently reported were smudged and apoptotic neutrophils and neutrophils with other dysplastic like changes like C shaped, ring-shaped, and fetus-like nuclei and nucleoplasmic elongations ( 30 , 31 , 36 , 37 ). Lymphocyte changes did not correlate with patients’ clinical course, but it has been suggested that COVID-19 could become a new aetiology for reactive lymphocytes and can maybe indicate the presence of SARS-CoV-2 before PCR confirmation ( 31 - 33 , 37 ).…”
Section: Introductionmentioning
confidence: 98%